Engineering Education Roadmap of the Future Trend of Basic Metaverse based on VR with cooperation between the government and the private sector - Boonchana Purahong; Thanavit Anuwongpinit; Isoon Kanjanasurat; Manit Chansuthirangkool; Kamphon Singto; Nuttakrit Somdock; Pattareeya Damrongsak; ParkPoom Khunthawiwone; Tuanjai Archevapanich (My University, 2022)
This article presents an educational roadmap of future trends of Metaverse in VR-based by collaborating between the School of Engineering, King Mongkut's Institute of Technology Ladkrabang (KMITL) with iMAKE company to make a part-time learning plan. The objectives were to measure the achievement and evaluate satisfaction with the development of part-time learning skills in technology on the topic “Basic Metaverse based on VR”. The sample group was students in a double-degree bachelor's degree program (Dual Degree) between the School of Engineering and the Faculty of Science, KMITL: Bachelor of Engineering (IoT System and Information Engineering) and Bachelor of Science (Industrial Physics) for 16 students by selecting a specific sample group, the engineering education program has a systematic process. The results showed that the achievement of part-time learning skills development in technology on the topic “Basic Metaverse based on VR” higher than the set criteria 74 %, the overall satisfaction is at a very good level, the mean satisfaction was 4.636 and the sample standard deviation was 0.39.
Keywords: Virtual Reality Applications and Impacts; Augmented Reality Applications; Engineering Education and Technology